Synthesis and Biological Activities of Some Thiazolidin-4-ones - Özadali, Keriman; Özkanli, Fügen; Erol, Dilek; Dogan, Ali Evrim; Erol, Kevser (Arzneimittelforschung, 2006)
In this study, fifteen 2,3-disubstituted-4-thiazolidinone derivatives were synthesized by the reaction of Schiff bases and α-mercaptoacetic acid. The structures of the compounds were elucidated by IR, 1H-NMR, 13C-NMR, mass spectral data and elementary analysis. The antihist aminic and anticholinergic activities of the compounds were determined by tests performed on isolated guinea pig trachea in comparison with aminophylline (CAS 317–34–0). Compound 15 (3-[3-(2-methylpiperidine-1-yl)propyl]-2-(4-methylphenyl)thiazolidin-4-one hydrochloride) showed the highest inhibition (53 %).
Keywords: Antihistaminic agents; Thiazolidin-4-ones, anticholinergic activity, antihistaminic activity, synthesis